G382(P) Brain white matter changes in four patients with classical homocystinuria: Two of them were reversible. (24th May 2017) - Hawli, M El; Masoud, H; Albahri, A; Refaat, M; Kini, V; Bashir, H El
Abstract : Background and objectives: Classical homocystinuria (CHU) due to Cystathionine Beta-Synthase (CBS) deficiency is rare autosomal recessive inborn error of amino acids metabolism causing accumulation of methionine and homocysteine. The estimated prevalence of CHU is between 1/20, 000 and 344, 000. However, in Qatar it is approximately 1/1, 800 births, the highest in the world. Brain white matter lesions unrelated to thromboembolic events are not commonly described in CHU. We present four patients with pyridoxine non-responsive CHU, who were found to have white matter changes on brain MRI, with a review of their clinical characteristics and neurological outcome. Methods: Retrospective review of medical records for four patients previously diagnosed with CHU. All patients had an underlying homozygous mutation of c.1006C>T (p.R336C) in the CBS gene and were diagnosed before the implementation of the National Metabolic Newborn Screening Program in Qatar. Results: Cerebral white matter changes were detected by brain MRI in all the four patients with pyridoxine non-responsive CHU whom had poor compliance to medication and diet restriction. In case (1) brain MRI was requested after signs of upper motor neuron lesion. Case (2) brain MRI was done due to history of headaches. In case (3), MRI brain was requested as a follow up for abnormal EEG findings. Finally, in case (4) brain MRI was done to investigate the complications of a road traffic accident. Hypermethioninemia was documented in all our patients with levels ranging between 600->1000 umol/L. We observed in two of our patients, case (2) and (3), that when blood methionine levels dropped because of better compliance, previously seen brain white matter changes were reversible. This supports the hypothesis of hypermethioninemia rather than Betaine treatment as the cause of the white matter changes. Conclusion: Our report confirms the finding of reversible cerebral white matter changes in poorly controlled patients with CHU. We stress on the importance of family/patient education to improve compliance with treatment and the dietary restriction to prevent serious complications. Further research is recommended to improve our understanding of the correlation between methionine levels the appearance of cerebral white matter changes, their progression and resolution.